UPAYA MASJID AGUNG SURAKARTA DALAM PELESTARIAN KOLEKSI NASKAH KUNO - Muhammad Ikhwan Fajar; Muhammad Ghozy Alfaruq; Mega Alif Marintan (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
The Great Mosque of Surakarta plays an important role in the history of islamic dissemination in the city of Surakarta. Along with the development of Islamic civilization in the region, numerous manuscripts were written by scholars, particularly graduates of Madrasah Mamba’ul ‘Ulum, an influential Islamic educational institution of its time. These ancient manuscripts contain various Islamic sciences and serve as evidence of intellectual heritage as well as part of the history of Islamic civilization in Surakarta. Most of these manuscripts have been donated to the Great Mosque of Surakarta and are currently managed by the mosque’s library as part of its responsibility in preservation efforts. This research aims to examine in depth the preservation efforts carried out by the Library of the Great Mosque of Surakarta. This study employs a qualitative method with a case study approach. Data were obtained through interviews, observations, and documentation. The results indicate that the library has undertaken various preservation efforts, including the digitization of some manuscripts, the development of a website for digital access, and collaboration with external parties, including academics and cultural preservation institutions. However, these preservation efforts have not been fully optimized due to several obstacles faced by the Great Mosque of Surakarta, such as limitations in human resources, infrastructure, and technology.